ANALISIS JARINGAN PIPA DISTRIBUSI AIR BERSIH DI DESA SRIMULYO KECAMATAN AIR SALEK KABUPATEN BANYUASIN - Priadi Priadi; Reni Andayani; Rosmalinda Permatasari; Ayu Marlina (LATERAL: Jurnal Teknik Sipil, 2023)
Srimulyo Village, Air Salek District has a water connection with PDAM Tirta Betuah as a clean water service provider. The problem that occurs is the lack of water pressure, so it cannot meet the need for clean water for 24 hours. Apart from loss of head, it is projected that there will be changes in population which will increase the burden on clean water capacity at the research location. This research was conducted to determine the existing clean water needs, population projections, and determine head loss. This calculation uses geometric methods to calculate population projections, as well as the Hardy Cross method to calculate pressure loss. In the drainage area in Srimulyo Village, the total need for clean water in 2022 is 371,760 lt/day, the projected population for the next 5 years in 2027 is 5,164 people, and in the next 10 years 2032 it is 6,435 people. And the loss of pressure height occurred in block 3, namely 6.03 m and the remaining pressure was 33.34 m. This is caused by a change in pipe diameter from 6 inches to 4 inches.